2016
DOI: 10.1113/ep085746
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and vitamin E together improve intestinal epithelial barrier function and alleviate oxidative stress in heat‐stressed pigs

Abstract: New Findings r What is the central question of this study?Oxidative stress may play a role in compromising intestinal epithelial barrier integrity in pigs subjected to heat stress, but it is unknown whether an increase of dietary antioxidants (selenium and vitamin E) could alleviate gut leakiness in heat-stressed pigs. r What is the main finding and its importance? Levels of dietary selenium (1.0 p.p.m.) and vitamin E (200 IU kg −1 ) greater than those usually recommended for pigs reduced intestinal leakiness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
119
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(128 citation statements)
references
References 27 publications
8
119
1
Order By: Relevance
“…However, numerous environmental factors, including HT, can lead to excessive apoptosis, which has a harmful effect on human and animal health. Previous studies indicated that ROS acted as an upstream molecule in the mitochondrial apoptotic pathway, and HT‐induced oxidative stress could cause apoptosis in the small intestine . Oxidative stress may therefore be the intermediate for HT‐induced excessive apoptosis and organ injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous environmental factors, including HT, can lead to excessive apoptosis, which has a harmful effect on human and animal health. Previous studies indicated that ROS acted as an upstream molecule in the mitochondrial apoptotic pathway, and HT‐induced oxidative stress could cause apoptosis in the small intestine . Oxidative stress may therefore be the intermediate for HT‐induced excessive apoptosis and organ injury.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that ROS acted as an upstream molecule in the mitochondrial apoptotic pathway, [12][13][14] and HT-induced oxidative stress could cause apoptosis in the small intestine. 15,16 Oxidative stress may therefore be the intermediate for HT-induced excessive apoptosis and organ injury. Although numerous studies reported that the HT effect led to oxidative stress in muscle 2,9,10 and intestine, 17 whether this issue occurred in the immune organ was still not known for certain and needed to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…An improved resistance against HS in pigs supplemented with selenium and vitamin E was reported in the review of Renaudeau et al (2012). More recently, Liu et al (2016), in a study carried out on pig, demonstrated that the increase of dietary vitamin E and Se was able to reduce the negative impact of HS on intestinal barrier integrity.…”
Section: Vitamins and Mineralsmentioning
confidence: 89%
“…The reduction in gastrointestinal blood flow greatly impairs the epithelial cells of the small intestinal villi and induces excessive apoptosis [5, 10, 11]. Recently, studies in multiple animal models have detected heat stress-induced apoptosis in small intestinal tissue and intestinal epithelial cells [5, 1214]. However, little is known about the biological mechanisms involved in heat stress-induced apoptosis in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in free radicals from ischemia can lead to ROS-related damage of the intestinal mucosa. Heat stress-related oxidative stress has been shown to cause apoptosis in the small intestines of both rats and pigs [5, 13, 14]. Therefore, oxidative stress may be the intermediate through which heat stress induces intestinal damage and may act upstream of apoptosis.…”
Section: Introductionmentioning
confidence: 99%